The Effect of Family-centered Empowerment on Quality of Life in Children with Hemophilia - Shahnaz Rostami; Soulmaz Namaki KHameneh; Bijan Keikhaei Dehdezi; Mohammad Hossein Haghighizadeh (Hamadan University of Medical Sciences, 2020)
Introduction: Quality of life is one of the influencing factors in children with hemophilia. The quality of life of children with hemophilia is affected by complaints of permanent pain, bleeding, and discomfort related to treatment complications. The aim of this study was to determine the effect of family-centered empowerment on quality of life of children with hemophilia in Ahvaz city in year 2018. Methods: In this quasi-experimental study, 50 children with hemophilia who referred to hematology clinic of Baqaei Hospital, Ahwaz, Iran, were randomly selected. The experimental group received 9 training sessions based on the family-centered empowerment model comprising four steps of threat perception, problem solving, educational participation and evaluation by the researcher with the presence of primary caregivers and children with hemophilia. The control group received only the routine care program. At baseline and one month after the intervention, both groups completed the demographic and quality of life questionnaire for hemophilic children. Data were analyzed using descriptive and inferential statistics (independent t-test, paired t-test, Fisher exact test, and Chi-square test) using SPSS 22. Results: The study showed no significant difference in total score of quality of life in children (P=0.444) before intervention between the two groups; but after the intervention a significant difference was observed in terms of quality of life (P=0.030) and family dimension (P=0.019), friends (P=0.015) and perceived support (P=0.011) between the two groups. Conclusion: According to the results of this study, it can be said that family-centered empowerment can be used as a low cost and easy way to improve the quality of life of hemophilia patients by nurses.